Authorization procedure for COVID-19 vaccines: United States of America, European Union and Latin America - Ruiz Sayritupac de Nué, María Esther; González Leonor, María del Carmen (Ars Pharmaceutica (Internet), 2022)
Introduction: The recognition of the COVID-19 disease as a pandemic posed a challenge to the National Drug Regulatory Authorities (NRAs). They had to develop guidelines, procedures, create working groups and partnerships to maximize the efficiency of vaccine evaluation, review and licensure. The aim of this article is to present the procedures used in the United States, European Union and Latin America to license the use of vaccines against COVID-19; in order to determine whether the multiplicity of procedures has led to the registration of a large number of vaccines. Method: A review of the pharmaceutical legislation used for the issuance of COVID-19 vaccines licenses during the health emergency was carried out. The information was collected up to October 15, 2022. The sources consulted were government websites of the NRAs: United States, European Union, and Latin America. Results: The United States and the European Union used activities included in their standard flows, such as pre-Investigational New Drug, scientific advice and rolling review, respectively. Latin America, on the other hand, made extensive use of reliance and emergency use authorization in order to access as many vaccines as possible. Conclusions: The procedures used are diverse, but all of them are oriented to provide a rapid pandemic containment product. This diversity results in the presence of different vaccines in the United States, European Union and Latin America.